Ethics and Legal Education - Brooks, Brian (Victoria University of Wellington Law Review, 1998)
The submission of the report by Brent Cotter QC and Christopher Roper on Education and Training in Ethics and Professional Responsibility to the New Zealand Law Society in 1994 highlighted the need for a concerted effort to inculcate ethical know-how into the profession at all stages of their education and practice. In this article Professor Brooks surveys the place of ethics in law teaching today and ponders the many problems surrounding the teaching of ethics in the university environment. He argues that the teaching of ethics needs to focus on the process and context of ethics rather than focussing on the rule based modfel which some commentators advocate.